Longitudinal Study on Dynamics and Determinants of Nutritional Status among Children Suffering from Tuberculosis in Purulia District of West Bengal - Ghosh, Pramit; Sengupta, Debjani; Dwivedi, Malvika (National Journal of Community Medicine, 2026)
Introduction: Malnutrition in children is a significant cause and risk factor for tuberculosis infection and mortality. This study tracked changes in nutritional parameters among tuberculous children in a public health context. Methodology: This longitudinal field-based study was conducted among assenting below 18 tuberculous children in Purulia, West Bengal Monthly anthropometric measurements were taken by trained healthcare workers, and biochemical parameters were recorded at baseline and the end. A weekly food diary was maintained for 24 weeks. Data was analyzed using R 4.4.1 and World Health Organization (WHO) Anthro software. Results: Of 32 recruited children, 2 died and 5 were excluded from the analysis, sample size at end of analysis was 17 with 50.0% having extra pulmonary tuberculosis. Four children were under 5 years of age. Analysis as per standardized Z score showed persistent malnutrition (<-1Z-score) for BMI for age and <-2Z for height-for-age, while weight-for-age improved from -0.04 Z to -0.02 Z. Statistically significant changes in hemoglobin levels in girls (p=0.007) were noted. The food diary indicated that children missed an average of one meal per day, particularly protein and green vegetables. Conclusion: Targeted nutritional interventions for children and support beyond treatment completion are necessary.